1986
DOI: 10.1126/science.3014648
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mononuclear Phagocytes in HTLV-III/LAV Infection

Abstract: Cells with properties characteristic of mononuclear phagocytes were evaluated for infectivity with five different isolates of the AIDS virus, HTLV-III/LAV. Mononuclear phagocytes cultured from brain and lung tissues of AIDS patients harbored the virus. In vitro-infected macrophages from the peripheral blood, bone marrow, or cord blood of healthy donors produced large quantities of virus. Virus production persisted for at least 40 days and was not dependent on host cell proliferation. Giant multinucleated cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
829
3
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,739 publications
(857 citation statements)
references
References 35 publications
24
829
3
1
Order By: Relevance
“…This finding is consistent with the knowledge that macrophages are a long-lived HIV reservoir, thereby providing a continuous source of virus for de novo infection of susceptible target cells that reside and/or circulate in the lymphoid tissue (35)(36)(37).…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with the knowledge that macrophages are a long-lived HIV reservoir, thereby providing a continuous source of virus for de novo infection of susceptible target cells that reside and/or circulate in the lymphoid tissue (35)(36)(37).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, we and others reported that the low dNTP pool in macrophages is partially due to active hydrolysis of cellular dNTPs by SAMHD1, a cellular dNTP triphosphohydrolase (5,6). Although the dNTP pools differ considerably, both cell types have similarly high concentrations of ribonucleoside triphosphates (rNTPs) 2 (4). In addition, it has been shown that this disparity exists in yeast (7).…”
mentioning
confidence: 99%
“…Human immunodeficiency virus type 1 (HIV-1) uniquely infects both activated CD4 ϩ T cells and terminally differentiated/ non-dividing macrophages (1,2). These cells differ in the concentrations of their intracellular deoxyribonucleoside triphosphates (dNTPs).…”
mentioning
confidence: 99%
“…The presence of an extravascular reservoir of human immunodeficiency virus type 1 (HIV-1)-infected macrophages is well established (6,7,10,12,30,31). The ability of tissue macrophages to serve as a reservoir for HIV-1 and simian immunodeficiency virus replication correlates with the ability of monocyte-derived macrophages to support productive viral infection in vitro (reviewed in reference 10).…”
mentioning
confidence: 99%